2017
DOI: 10.1080/00949655.2017.1365148
|View full text |Cite
|
Sign up to set email alerts
|

On structure, family and parameter estimation of hierarchical Archimedean copulas

Abstract: Research on structure determination and parameter estimation of hierarchical Archimedean copulas (HACs) has so far mostly focused on the case in which all appearing Archimedean copulas belong to the same Archimedean family. The present work addresses this issue and proposes a new approach for estimating HACs that involve different Archimedean families. It is based on employing goodness-of-fit test statistics directly into HAC estimation. The approach is summarized in a simple algorithm, its theoretical justifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Assuming λ( ) and λ( ) to belong to a one-parametric family of generators (or possibly to two di erent one-parametric families of generators), which is a common assumption in many applications of HACs, for a lot of families, it follows that τ = τ implies that C λ( ) = C λ( ) , e.g., cf. Tables 1, 2 and 3 in [3]. Hence, applying this assumption, it follows that…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Assuming λ( ) and λ( ) to belong to a one-parametric family of generators (or possibly to two di erent one-parametric families of generators), which is a common assumption in many applications of HACs, for a lot of families, it follows that τ = τ implies that C λ( ) = C λ( ) , e.g., cf. Tables 1, 2 and 3 in [3]. Hence, applying this assumption, it follows that…”
Section: Discussionmentioning
confidence: 94%
“…There, the approach denoted kt_kagg, originally proposed in [2] and merged with an approach to collapsing of HAC structures from [14], has shown the best results in the ability to estimate the true structure of a HAC among the 11 estimators considered. Also note that in [3], the kt_kagg approach was improved by a new approach to collapsing HAC structures and re-estimation of the parameters, which is con rmed in the simulation study reported therein. In the same article, the authors also show that a structure obtained by this improved kt_kagg satis es the su cient nesting condition, which guarantees that a proper copula results, under relatively weak conditions provided the families of the Archimedean generators in the structure are all the same.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations